Nuansa Spiritual dan Healing Sufistik: Aplikasi Penafsiran Isyari al-Qusyairi dalam Tafsir Lathif al-Isyarat dan Penerapannya pada Santri di Pondok Pesantren Ahlussunnah Waljamaah NW Lombok Timur - Zaki, Muhammad; Ridho, Abdul Rasyid (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study aims to investigate the influence of applying the interpretation of Isyari al-Qusyairi in Tafsir Lathif al-Isyarat on spiritual nuances and sufistic healing processes among students (santri) at Pondok Pesantren Ahlussunnah Waljamaah NW in East Lombok. The research method employed is qualitative with a case study approach. Data collection techniques involve in-depth interviews with the pesantren management, religious teachers (ustadz), and santri who have experienced these spiritual practices. Data is also gathered through participatory observation of religious activities and small group discussions at the pesantren. Data analysis is conducted using a thematic approach, where qualitative data is analyzed to identify patterns and themes related to the spiritual experiences and behavioral changes of santri after applying the teachings of Isyari al-Qusyairi. The results indicate that these spiritual practices enhance spiritual awareness and emotional well-being among santri, while deepening their understanding of sufistic teachings. In conclusion, the study finds that the interpretation of Isyari al-Qusyairi in Tafsir Lathif al-Isyarat effectively creates profound spiritual nuances and provides a healing mechanism for santri. The implication of this research underscores the importance of integrating sufistic teachings in pesantren education to enhance the spiritual quality and mental well-being of santri.